Multiply each term by a^2b^2:-
b^2y^2 + a^2x^2 = a^2b^2
subtract a^2x^2 from both sides
b^2y^2 = a^2b^2 - a^2x^2
Now divide both sides by b^2
y^2 = a^2 - a^2x^2 / b^2 = a^2 (1 - x^2/b^2)
take positive square root ( because y > 0)
y = a sqrt(1 - x^2/b^2)
Answer to the question
-20
Answer: -(1/4)^3
Step-by-step explanation:
Equals -1/64 which is -64
how many pounds does he feed his dogs for each meal?
Use the formula i = p*r*t.
Here, p = $100000, r = 0.05 and t = 1 (year)
The interest would be i = $100000*0.05*1 = $5000 per year.